Implementasi Strategi Pemasaran Pendidikan di Madrasah - Dian; Ilis Rosbiah; Ari Prayoga (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
Competition between educational institutions, especially the private sector in order to get new students is very tight, this can be seen by the many educational institutions that implement marketing strategies to attract as many students as possible. This study aims to reveal the implementation of educational services marketing strategies with the foundation of management theory and marketing mix in Madrasah Aliyah Miftahurroja Lebakmuncang-Ciwidey, Indonesia. The method used in this research is descriptive with a qualitative approach. Collecting data in this study are, observations of the internal and external environment of madrasas, interviews with madrasah heads, deputy heads of curriculum, educators, committee, and pamphlet study documents, list of institutions, madrasah marketing agenda. Data analysis techniques used are to do data reduction, data presentation, and drawing conclusions. The results of this study indicate that: first, the marketing strategy of education services to improve the quality of education in MA Miftahurroja Lebakmuncang Ciwidey by using the management function, there are four stages, namely Planning, organizing, implementing and evaluating. Secondly, the implementation of an education services marketing strategy in MA Miftahurroja Lebakmuncang through marketing mix namely; products, places, prices, promotions, people, physical evidence, and processes. The competitiveness of MA Miftahurroja Lebakmuncang Ciwidey is good enough, it can be seen from the data of the increasing number of students.